MINIMALISASI TAX EVASION MELALUI TARIF PAJAK, TEKNOLOGI DAN INFORMASI PERPAJAKAN, KEADILAN SISTEM PERPAJAKAN, DAN KETEPATAN PENGALOKASIAN PENGELUARAN PEMERINTAH (Studi Empiris pada Wajib Pajak Orang Pribadi di Wilayah KPP Pratama Pekanbaru Senapelan) - Inggrid Permatasari; Herry Laksito (Diponegoro Journal of Accounting, 2013)
Tax revenues are very important in securing the state budget and the balance between national economic conditions and the global economic unification. However, in reality there are many taxpayers who do not obey the tax laws by doing tax evasion. This study aimed to describe and analyze the influence of perception on tax rates, technology and information og taxation, taxation fairness, and accuracy allocation of government expenditure to minimize tax evasion.The research was conducted by survey method to individual taxpayers in Pekanbaru, which is obtained by incidental sampling. Data collection method used surveys and questionnaires, and then the data were analyzed using descriptive analysis and multiple regression analysis.The results of this study prove that the tax rates have a positive and significant impact on tax evasion, and technology and information of taxation, taxation fairness and accuracy allocation of government expenditure have a negative and significant impact on tax evasion, both partial and simultaneous. Variable tax rates provide the greatest influence on tax evasion because it has a beta value of 0,22 while the variable technology and information of taxation provide the smallest influence on tax evasion because it has a beta value of -0.01. Variable tax rates, and technology and information of taxation, taxation fairness, and the accuracy allocation of government expenditure can be used to describe tax evasion of 78%.